Effect of injection time on combustion, performance and emission characteristics of direct injection CI engine fuelled with equi-volume of 1-hexanol/diesel blends. (1st January 2021) - Santhosh, K.; Kumar, G.N.
Abstract: In this experimental research work, the effect of 1-Hexanol on engine parameters is studied and to improve the combustion, performance and emission characteristics of CI engine, fuel injection time is advanced and retarded to know the best possible injection time. The experiment is conducted in a twin-cylinder, common rail direct injection diesel engine, speed (2000 rpm) of the engine is constant throughout the experiment and the engine load is varied as 20%, 40%, 60% and 80%. In this experiment equi-volume of 1-Hexanol/diesel blends is used as a fuel, the experiment is conducted for standard (12°BTDC), advanced (15°BTDC) and retard (9°BTDC) injection time. The obtained results are compared with baseline readings taken at standard injection time. The advanced injection time shows the best results compared to standard and retard injection time. The advanced injection time shows improved combustion parameters, the combustion peak moves near to TDC. An increment of 14.28% in BTE is noted for 1-Hexanol blend. The CO and HC emission decreases with advanced injection time, whereas higher NOx emission is noted. It is concluded that 50% of 1-Hexanol can be used in CI engine with slight modification in injection time; the advanced injection time gives improved efficiency. Highlights: Impact of 1-Hexanol/diesel blends on engine chractestics are examined in a CRDI CI engine. The advanced injection time improves the combustion, performance and emission parameter. 1-Hexanol/diesel blends increases the BTE, NOx and reduces the BSEC, CO and HC at 15°BTDC compared to standard injection time. At 80% load, an 8.33% increment in BTE is noted for 50H50D at advanced injection time compared to standard injection time.